Aerodynamic effect of an alula-like vortex generator using pressure sensitive paint technique - Chung, Ping-Han; Yeh, Szu-I (Frontiers in Physics, 2023)
Herein, the pressure-sensitive paint (PSP) was used to quantitatively investigate the aerodynamic effect of an alula-like vortex generator, which is a bio-inspired passive flow control structure. The global pressure distributions on the upper surface at different angles of attack were measured to determine the strength of sectional suction forces on the wing. An alula-like vortex generator equipped at the leading edge of the wing enlarged the area of the suction region (negative pressure coefficient) on the upper surface in both the streamwise and spanwise directions under near-stall and deep-stall conditions, which is related to the generation of lift and avoiding the stall of the wing. A wing model equipped with a vortex generator of an 11% height/chord length ratio exhibited the greatest performance at all angles of attack. In this study, the use of PSP technique not only helps to understand the aerodynamic effect of the alula-like vortex generator but also shows a perspective tool for bio-inspired MAVs design.